Telomere length in young and middle-aged patients: relationship with cardiovascular risk factors - V. I. Podzolkov; A. E. Bragina; N. A. Druzhinina; L. V. Vasilyeva; R. A. Shikhmagomedov; E. M. Averyeva (Российский кардиологический журнал)
Aim. To evaluate the relationship between leukocyte telomere length (LTL) and cardiovascular risk factors in young and middle-aged patients without cardiovascular disease (CVD).Material and methods. This cross-sectional study involved 450 patients aged 30 [21;42] years. Risk factors and possible exclusion criteria was assessed through questionnaires and anthropometric examination. In all subjects, glucose concentration and lipid profile were assessed using the CardioChekPA express analyzer (USA, 2017), followed by calculation of integral metabolic indices: visceral adiposity index (VAI), body fat percentage, body adiposity index (BAI), lipid accumulation product (LAP). LTL was measured in whole blood samples using fluorimetry (Qubit 4 Singapore 2020) and reverse transcription polymerase chain reaction (QIAamp Blood Mini Kit, German 2022). Statistical analysis was carried out using the Statistica 10 program.Results. The prevalence of the studied risk factors in the main group corresponded to the general population. According to the correlation analysis, LTL was associated with age (r=-0,26; p<0,05), smoking (r=-0,35; p<0,05), obesity (r=-0,19; p>0,05), neck circumference (NC) (r=-0,53; p<0,05), diastolic blood pressure (r=-0,31; p<0,05), cholesterol (r=-0,64; p<0,05), high-density lipoproteins (HDL) (r=0,59; p<0,05) and low-density lipoproteins (r=-0,52; p<0,05), triglycerides (r=-0,46; p<0,05), glucose (r=-0,33; p<0,05), LAP (r=-0,4; p<0,05), VAI (r=-0,57; p<0,05) and BAI (r=-0,32; p<0,05). According to the multivariate regression analysis, LTL was associated with age (B=-0,04, Std. Err. of B=0,02, p=0,03), smoking (B=-0,87, Std. Err. of B=0,26, p=0,001), NC (B=-0,23, Std. Err. of B=0,07, p=0,001), total cholesterol levels (B=-0,37, Std. Err. of B=0,87, p<0,001), HDL (B=0,59, Std. Err. of B=0,24, p=0,018), LAP (B=-0,01, Std. Err. of B=0,02, p<0,011), VAI (B=-0,37, Std. Err. of B=0,16, p=0,025).Conclusion. LTL is interconnected with cardiovascular risk factors, which determines the significance of their participation in CVD development and biological aging in young and middle-aged people.